Vitamin A Metabolism During Refractory Telogen. (29th May 2020) - Hovland, Damla; Suo, Liye; Kedishvili, Natalia; Sundberg, John; Everts, Helen
Abstract: Objectives: Hair follicles cycle through periods of growth (anagen), regression (catagen) and rest (telogen). Telogen is further divided into refractory and competent telogen based on the expression of bone morphogenetic protein 4 (BMP4). Previously, the expression of a complete set of proteins involved in retinoic acid (RA) synthesis and signaling localized to the hair follicle and changed throughout the hair cycle. In addition, excess dietary vitamin A arrested the hair cycle in telogen; while retinol dehydrogenases short-chain dehydrogenase/reductase family 16C members 5 and 6 ( Sdr16c5 − / − /Sdr16c6 − / − ) double null mice had an accelerated the hair cycle. The purpose of this study was to further define these changes in the hair cycle. Methods: The localization of RA synthesis proteins SDR16C5, retinol dehydrogenase 10 (RDH10), retinal dehydrogenase 2 (ALDH1A2), cellular RA binding protein 2 (CRABP2), RA degradation enzyme cytochrome p450 26B1 (CYP26B1), and BMP4 was examined in telogen hair follicles in female C57BL/6 J mice by immunohistochemistry. Immunohistochemistry with an antibody against BMP4 was also used to mark refractory telogen in the previous dietary vitamin A study. Results: All proteins localized to BMP4 positive refractory telogen hair follicles. SDR16C5 and ALDH1A2 were also seen in BMP4 negative competent telogen hair follicles, but at a lower level. RDH10 was expressed in both BMP4 negative and positive hair follicles at similar levels. BMP4 expression was also used to distinguish refractory from competent telogen in C57BL/6 J mice fed different levels of vitamin A. Both low and excess dietary vitamin A resulted a greater percentage of hair follicles in refractory telogen in different studies. Conclusions: In conclusion, RA synthesis and signaling may be stronger in refractory telogen and contribute to the inhibition of the hair cycle. Funding Sources: NIH/NIAMS, Internal funding.